Programming of growth hormone secretion and bone mineral density in elderly men: a hypothesis. - Fall, C; Hindmarsh, P; Dennison, E; Kellingray, S; Barker, D; Cooper, C (1998)
Epidemiological studies suggest that retarded growth in infancy is associated with low adult bone mass. The mechanism underlying this association is unknown, but the programming of GH secretion or sensitivity by environmental influences during early development may play a role. We examined this issue in a sample of 37 healthy men, aged 63-73 yr, whose weight gain in infancy had been recorded. Venous blood samples were obtained under standard conditions every 20 min over a 24-h period. Measurements were made of the GH secretory profile, insulin-like growth factor I (IGF-I), IGF-binding protein-1 and -3, and GH-binding protein. Bone mineral density was measured at the lumbar spine and femoral neck using dual energy x-ray absortiometry. There was a statistically significant association between peak GH concentration (r = 0.46; P < 0.01) and fasting IGF-I concentration (r = 0.46; P < 0.01) with femoral neck bone density. After allowing for the peak GH concentration, median GH was negatively (P < 0.05) associated with bone mineral density. Weight at 1 yr was not related to peak GH, but was strongly related to the median GH concentration (r = 0.42; P = 0.01). These observations are consistent with a dual effect of GH secretion on bone density. High peak GH values drive IGF-I production and maintain bone mineralization in adult life. However, integrated GH secretion, after adjusting for the effect of pulse amplitude, is negatively associated with bone density in adult life. This particular characteristic of the GH secretory profile correlates with growth during infancy and might be programmed by environmental factors during intrauterine or early postnatal life.